Design Of Project Based Learning In Islamic Religious Education For The Development Of Religious Character - Risal Qori Amarullah; Aan Hasanah; Badrudin Badrudin; Hariman Surya Siregar (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
Abstract: Character education has become a critical challenge in secondary education, particularly in learning contexts that emphasize cognitive achievement over affective and behavioral development. Although Project-Based Learning (PjBL) is widely recognized for its potential to foster collaboration and responsibility, character outcomes are often treated implicitly and rarely evaluated systematically. This study aims to develop and evaluate a character-oriented Project-Based Learning framework using a Design-Based Research (DBR) methodology in Islamic secondary education. The research was conducted through iterative design cycles involving problem analysis, instructional design, implementation, evaluation, and refinement. Explicit character indicators were embedded into each phase of the PjBL process and assessed using quantitative and qualitative instruments. Statistical analysis of pretest and posttest data revealed significant improvements in students’ character-related outcomes following the implementation of the proposed framework. Qualitative findings further indicated enhanced student engagement, collaboration, and social responsibility during project activities. The results demonstrate that integrating explicit character indicators into PjBL through a DBR approach enhances the effectiveness of character education beyond conventional instructional practices. This study contributes to the literature by providing a structured and empirically validated framework that bridges Project-Based Learning, Design-Based Research, and character education. The proposed framework offers practical implications for educators seeking to integrate affective learning objectives into active learning environments.